Genotoxic assessment of chlorhexidine mouthwash on exfoliated buccal epithelial cells in chronic gingivitis patients - Saif Khan; Asad Ullah Khan; Sadaf Hasan (Wolters Kluwer Medknow Publications, 2016)
Background: Chlorhexidine (CHX) is the gold standard of all chemical plaque control agents and the most commonly prescribed mouthwash. However, several studies have shown cytotoxic and genotoxic effects of CHX on various eukaryotic cells. In this study, we have used micronuclei as a biomarker of DNA damage in buccal epithelial cells of chronic gingivitis patients who were given adjunct 0.2% CHX for plaque control. Materials and Methods: Chronic gingivitis patients who were exclusively on mechanical plaque control methods were taken as control (Group A) (n = 101), and chronic gingivitis patients who along with mechanical plaque control measures were taking 0.2% chlorhexidine mouthwash as adjunct were taken as cases (Group B) (n = 255). The Group B was further divided into 5 subgroups (B1, B2, B3, B4, B5) (n = 51) on increasing duration of usage of CHX from ≤1 week to 24 weeks. Buccal epithelial cells were gently scrapped from the buccal mucosa using soft toothbrush. The epithelial cells were collected in buffer solution and centrifuged at 8000 rpm for 5 min. The buccal epithelial cells were air dried, fixed, and stained with 5% Giemsa stain on preheated glass microscopic slides and observed under microscope to screen 2000 nucleated cells per individual for number of micronucleated cells and micronuclei as genotoxic measure. Results: The mean number of micronucleated cells was found to be 0.41 ± 0.71 for Group A as compared values ranging from 1.65 ± 2.09 (Group B1) to 11.7 ± 1.87 (Group B5) in different subgroups of Group B, and similarly, the mean number of micronuclei was found to be 0.48 ± 0.80 for Group A as compared to values ranging from 2.57 ± 1.64 (Group B1) to 14.5 ± 2.49 (Group B5) in different subgroups of Group B using analysis of variance (P < 0.001). Conclusion: We conclude that CHX mouthwash is genotoxic to buccal epithelial cells and there is incremental trend in genotoxicity as the duration of usage is increased.